2006
DOI: 10.1111/j.1365-2435.2006.01097.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost of prolonged diapause and its relationship to body size in a seed predator

Abstract: Summary 1.Although metabolic resource losses are maintained at low rates during diapause, the accumulation of losses over a long period negatively affects organisms with prolonged diapause usually extending beyond 1 year. The seed-predatory weevil Exechesops leucopis (Jordan) (Coleoptera: Anthribidae) enters winter diapause at the final-instar larval stage within seeds of Styrax japonica Sieb. et Zucc. (Styracaceae) at a density of one larva per seed. After diapause, larvae pupate within the seeds and then eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 18 publications
3
51
1
1
Order By: Relevance
“…Results of the present study indicated increasing in the mortality percentages of the exit diapused larvae, a lower fecundity and lower fertility. It has been recorded previously a lower post-diapause survival and reduced fecundity (Ellers and van Alphen, 2002;Williams et al, 2003;Munyiri et al, 2004;Matsuo, 2006). Finally, PBW is the key pest in the cotton-producing areas of the world which affects the cotton yield in several ways.…”
Section: Resultsmentioning
confidence: 99%
“…Results of the present study indicated increasing in the mortality percentages of the exit diapused larvae, a lower fecundity and lower fertility. It has been recorded previously a lower post-diapause survival and reduced fecundity (Ellers and van Alphen, 2002;Williams et al, 2003;Munyiri et al, 2004;Matsuo, 2006). Finally, PBW is the key pest in the cotton-producing areas of the world which affects the cotton yield in several ways.…”
Section: Resultsmentioning
confidence: 99%
“…In several insect species, diapause is longer in larger individuals (Bakke, 1971;Nesin, 1985;Powell, 1989;Danforth, 1999;Menu & Desouhant, 2002;Matsuo, 2006). For example, in the chestnut weevil Curculio elephas (Menu & Desouhant, 2002), the bee Perdita portalis (Danforth, 1999) and the seed-predatory weevil Exechesops leucopis (Matsuo, 2006), the probability of prolonged diapause increases with higher larval weight.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the chestnut weevil Curculio elephas (Menu & Desouhant, 2002), the bee Perdita portalis (Danforth, 1999) and the seed-predatory weevil Exechesops leucopis (Matsuo, 2006), the probability of prolonged diapause increases with higher larval weight. Such extra metabolic resources, associated with low energy consumption during prolonged diapause (Danks, 1987), could ensure higher fecundity of the long-cycle phenotype and consequently, could compensate for the cost of prolonged diapause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although aphids inside the galls perhaps may not enter "diapause" in its physiological sense, this phenomenon is akin to prolonged (or delayed) diapauses, which are known in various insect groups [38] such as weevils [39][40][41], gall midges [42], and carnid flies [43], and often are interpreted as a bet-hedging adaptation [39]. In the case of N. monzeni, it is also possible that gall inhabitants may avoid competition for nutrition within a yearly cohort that has formed galls on the same or nearby buds.…”
Section: Why Such a Long Life Cycle?mentioning
confidence: 99%